2021
DOI: 10.3390/atmos12091109
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Chemical Composition of Road Dust in Two High-Altitude Latin American Cities

Abstract: Road dust (RD) resuspension is one of the main sources of particulate matter in cities with adverse impacts on air quality, health, and climate. Studies on the variability of the deposited PM10 fraction of RD (RD10) have been limited in Latin America, whereby our understanding of the central factors that control this pollutant remains incomplete. In this study, forty-one RD10 samples were collected in two Andean cities (Bogotá and Manizales) and analyzed for ions, minerals, and trace elements. RD10 levels vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The megacity had a high motorization rate during the study period (313 vehicles/1000 inhabitants). The vehicle fleet during the study period was 2.5 million vehicles, distributed as follows: passenger cars = 46%, pickup truck = 25%, motorcycles = 22%, heavy trucks = 3%, taxis = 2%, and public transport buses = 2% [43]. Private vehicles and motorcycles use mainly gasoline, taxis use natural gas and gasoline, buses use natural gas and diesel, and heavy vehicles use mainly diesel [44].…”
Section: Study Sitementioning
confidence: 99%
“…The megacity had a high motorization rate during the study period (313 vehicles/1000 inhabitants). The vehicle fleet during the study period was 2.5 million vehicles, distributed as follows: passenger cars = 46%, pickup truck = 25%, motorcycles = 22%, heavy trucks = 3%, taxis = 2%, and public transport buses = 2% [43]. Private vehicles and motorcycles use mainly gasoline, taxis use natural gas and gasoline, buses use natural gas and diesel, and heavy vehicles use mainly diesel [44].…”
Section: Study Sitementioning
confidence: 99%
“…The study found that Igeo values of HMs in the RD samples decreased in the following order: Mo > Cu > Zn > Pb > Cr > Fe > Mn > Co, considering that the highest Igeo value was observed for Mo at the locality of Q14 (Igeo = 4.46, heavily to extremely contaminated) (Fig, 4). This high contamination grade for Mo can be referred significantly to brake pad abrasion (Vanegas et al, 2021;Wiseman et al, 2021), as in general, the brake discs are made up of Fe (about 95%), silica (about 2%), and Mo (about 0.2%) (Hulskotte et al, 2014), regarding the great contribution made by braking-related emissions in the total traffic emissions, with ratios up to 50, 12, and 70% in PM10, PM2.5, and total braking-related emissions, respectively (Bozlaker et al, 2014;Harrison et al, 2012;Hulskotte et al, 2014). Being a geochemical signature for contamination from traffic sources, the comparatively higher Igeo values observed for Cu, Zn, and Pb were mainly attributed to traffic-related emissions (e.g., the deposition of exhaust particles from vehicles) followed by industrial emissions (Aguilera et al, 2021;Choi et al, 2020;Shahab et al, 2020).…”
Section: Pollution and Ecological Risk Assessment Of Hms In Road Dustmentioning
confidence: 99%